Helicobacter pylori Outer Membrane Vesicle Proteins Induce Human Eosinophil Degranulation via a β2 Integrin CD11/CD18- and ICAM-1-Dependent Mechanism - Su Hyuk Ko; Jong Ik Jeon; Young-Jeon Kim; Ho Joo Yoon; Hyeyoung Kim; Nayoung Kim; Joo Sung Kim; Jung Mogg Kim (Hindawi Limited, 2015)
Eosinophil cationic protein (ECP), a cytotoxic protein contained in eosinophils granules, can contribute to various inflammatory responses. Although Helicobacter pylori infection increases infiltration of eosinophils, the mechanisms of eosinophil degranulation by H. pylori infection are largely unknown. The goal of this study was to investigate the role of H. pylori outer membrane vesicles (OMVs) in modulating eosinophil degranulation. We found that eosinophils treated with H. pylori OMVs released significantly more ECP compared with untreated controls. In addition, eosinophils cocultured with OMV-preexposed primary gastric epithelial cells exhibited significantly increased ECP release. Similarly, eosinophils cocultured with culture supernatant (CM) from primary gastric epithelial cells exposed to OMVs (OMV-CM) released significantly higher amounts of ECP compared with eosinophils cocultured with CM from unexposed control cells. Furthermore, OMVs and OMV-CM both induced the upregulation of ICAM-1 on gastric epithelial cells and β2 integrin CD11b on eosinophils. In addition, both transduction of ICAM-1 shRNA into gastric epithelial cells and treatment with neutralizing mAbs to CD18 significantly decreased OMV-mediated or OMV-CM-mediated release of ECP. These results suggest that the eosinophil degranulation response to H. pylori OMVs occurs via a mechanism that is dependent on both β2 integrin CD11/CD18 and ICAM-1.